Biomarkers of sepsis-induced coagulopathy: diagnostic insights and potential therapeutic implications - Anaïs Curtiaud; Toshiaki Iba; Eduardo Angles-Cano; Ferhat Meziani; Julie Helms (Annals of Intensive Care)
Abstract Diagnosing coagulopathy in septic patients remains challenging in intensive care. Disseminated intravascular coagulation (DIC) indeed presents with complex pathophysiology, complicating timely diagnosis. Epidemiological data indicate a significant prevalence of DIC in septic patients, with mortality rates up to 60%. Despite advances, current biomarker-based diagnostic tools often fail to provide early and accurate detection. This review evaluates the utility and limitations of traditional and emerging biomarkers for diagnosing sepsis-induced coagulopathy (SIC) and DIC. We also assess the effectiveness of anticoagulant therapy guided by biomarker-based diagnostic criteria.